Systematic Review: Pengaruh Berjalan Setelah Makan terhadap Glukosa Postprandial Penderita Diabetes Melitus Tipe 2 - Anggia Skynta Febrianty; Muhamad Faishal Ramadhan; Ieva B Akbar; Fajar Awalia Yulianto (UNISBA Press, 2022)
Abstract. Diabetes mellitus is a serious health problem, because it is expected to continue to increase in the next twenty years, and more than 70% of patients will appear in developing countries. Postprandial glucose has a major role in glycemic control. One of the important methods of treating type 2 diabetes mellitus (DMT2) is increasing physical activity. Walking is a physical activity that almost everyone can do. The purpose of this study was to assess the effect of walking after eating on the control of postprandial blood sugar levels in patients with T2DM. This study uses a method systematic review from the database Pubmed, Springerlink, Sciencedirect, and Proquest with keywords (Adult OR Aged) AND